2018
DOI: 10.1161/circinterventions.117.006229
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Chronic Total Occlusion Interventions in Europe

Abstract: Background: The study focuses on the evolution of practice, procedural outcomes, and in-hospital complications of chronic total occlusion percutaneous coronary intervention in Europe. Methods and Results: Data from 17 626 procedures enrolled in European Registry of Chronic Total Occlusion between January 2008 and June 2015 were assessed. The mean patient age was 63.9±10.9 years; 85% were men. Procedural success increased from 79.7% to 89.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 28 publications
6
63
2
18
Order By: Relevance
“…Since the adoption of the hybrid approach and increased use of retrograde techniques, success rates have increased along with lesion complexity. Several studies have found current success rates between 70% and 85% [2,[12][13][14]. In accordance with these registry results, we found an excellent rate of in-hospital major adverse cardiac events of less than 1%.…”
Section: Discussionsupporting
confidence: 90%
“…Since the adoption of the hybrid approach and increased use of retrograde techniques, success rates have increased along with lesion complexity. Several studies have found current success rates between 70% and 85% [2,[12][13][14]. In accordance with these registry results, we found an excellent rate of in-hospital major adverse cardiac events of less than 1%.…”
Section: Discussionsupporting
confidence: 90%
“…The introduction of the retrograde approach has led to a successful rate of revascularization of approximately 90%. 43 The first step in the retrograde approach is to pass the collaterals.…”
Section: Retrograde Approachmentioning
confidence: 99%
“…Ähnliche Ergebnisse fanden sich im amerikanischen OPEN-CTO [23] und europäischem RECHARGE-Register [24], mit jeweils 86 % technischem Erfolg und sogar 89 %iger Erfolgsrate im Japanischem J-CTO-Register [25]. Die unlängst veröffentlichten Daten [26] des weltweit größten Register, des europäischen EuroCTO-Registers, mit über 17 000 behandelten CTO-Patienten, zeigen einen Anstieg der prozeduralen Erfolgsrate von 79,7 % im Jahr 2008 bis auf 89,3 % im Jahr 2015.…”
Section: Erfolgsaussichten Und Risikenunclassified